Aid During Conflict Interaction Between Military and Civilian Assistance Providers in Afghanistan, September 2001-June 2002 - Oliker, Olga (RAND Corporation, 2004)
Description and evaluation of relief, reconstruction, humanitarian, and humanitarian-type aid efforts in Afghanistan during the most intense phase of military operations, from September 2001 to June 2002. The efforts were generally successful, but there were serious coordination problems among the various civilian and military aid providers. Critical issues, both positive and negative, are identified, and a list of recommendations is provided for policymakers, implementers, and aid providers, based on lessons learned.